2004
DOI: 10.1128/aac.48.12.4673-4679.2004
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Human Antimicrobial Peptide LL-37 by Staphylococcus aureus -Derived Proteinases

Abstract: Cathelicidin LL-37 is one of the few human bactericidal peptides with potent antistaphylococcal activity. In this study we examined the susceptibility of LL-37 to proteolytic degradation by two major proteinases produced by Staphylococcus aureus, a metalloproteinase (aureolysin) and a glutamylendopeptidase (V8 protease). We found that aureolysin cleaved and inactivated LL-37 in a time-and concentration-dependent manner. Analysis of the generated fragments by mass spectroscopy revealed that the initial cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
378
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(398 citation statements)
references
References 50 publications
6
378
0
7
Order By: Relevance
“…Because no gene immediately adjacent to the PSMs showed clear homology to known proteinases, we explored the potential contribution of the well studied zinc-dependent S. aureus metalloprotease aureolysin. Previous studies have shown that aureolysin is promiscuous in its enzymatic activity, with the ability to cleave its own extracellular cell wall proteins, the human-derived antimicrobial peptide LL-37, and several other substrates (30,31).…”
Section: Imaging Mass Spectrometry Of Ca-mrsa-mentioning
confidence: 99%
“…Because no gene immediately adjacent to the PSMs showed clear homology to known proteinases, we explored the potential contribution of the well studied zinc-dependent S. aureus metalloprotease aureolysin. Previous studies have shown that aureolysin is promiscuous in its enzymatic activity, with the ability to cleave its own extracellular cell wall proteins, the human-derived antimicrobial peptide LL-37, and several other substrates (30,31).…”
Section: Imaging Mass Spectrometry Of Ca-mrsa-mentioning
confidence: 99%
“…To date, in S. aureus, three types of mechanism that affect susceptibility to antimicrobial peptides have been identified. These are (1) trapping defensins by binding to staphylokinase (Braff et al, 2007;Jin et al, 2004), (2) digestion of peptides by proteinase (Sieprawska-Lupa et al, 2004), and (3) changing the bacterial cell surface charge via dlt and mprF (Li et al, 2007a;Peschel et al, 1999Peschel et al, , 2001. mprF was first identified as fmtC, which was shown to affect the meticillin-resistance level in MRSA (Komatsuzawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SA positive for QuacA may exhibit higher levels of resistance to a cationic AMPs, as demonstrated experimentally for the platelet-derived AMP, tPMP [33]. The metalloprotease aureolysin is released by SA and can degrade human cathelicidin LL-37 in a dose and timedependent manner [34]; strains producing lower levels of aureolysin were found to be more susceptible to cathelidicin killing. A proteolytic activty released by SA also inactivates lactoferricin B, a cationic AMP derived from the N-terminus of mammalian lactoferrin [35].…”
Section: Infections Due To Microbial Resistance To the Innate Immunementioning
confidence: 98%